Eksplorasi Mindfulness Pada Mahasiswa Student Mobility UIN Surakarta Dalam Menghadapi Culture Shock Di Thailand Selatan - Zahra Nur Angraini; Isnanita Noviya Andriyani (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
This study aims to explore the application of mindfulness techniques by students of the Faculty of Ushuluddin and Dakwah at UIN Surakarta in coping with culture shock during a student mobility program in Southern Thailand. The method used is a qualitative approach with a phenomenological design, which allows the researcher to explore students’ subjective experiences in facing cultural challenges and to identify how mindfulness is applied in the adaptation process. The participants consisted of four students who took part in the mobility program and were selected through a culture shock scale distributed via Google Forms. Data collection techniques involved in-depth interviews and observation of students' experiences. The results of the study show that students applied mindfulness through five main forms: observing mental processes and external stimuli, describing experiences using accurate words, acting mindfully by being fully engaged in activities without distraction, non-judging inner experiences by accepting feelings and thoughts without criticism, and non-reactivity to inner experiences by avoiding automatic or reactive responses to events. These mindfulness techniques proved helpful in overcoming anxiety, confusion, and difficulties in adapting to the culture of Southern Thailand, as well as in enhancing calmness, patience, and openness to new environments. The effectiveness of mindfulness in overcoming culture shock was influenced by self-awareness and social support factors. This study concludes that mindfulness plays a significant role in helping students cope with culture shock and accelerates their adaptation process while studying abroad.